The role of interleukin-15 in the development and treatment of hematological malignancies - Sindaco, Paola; Pandey, Hritisha; Isabelle, Colleen; Chakravarti, Nitin; Brammer, Jonathan Edward; Porcu, Pierluigi; Mishra, Anjali (Frontiers in Immunology, 2023)
Cytokines are a vital component of the immune system that controls the activation and growth of blood cells. However, chronic overexpression of cytokines can trigger cellular events leading to malignant transformation. The cytokine interleukin-15 (IL-15) is of particular interest, which has been shown to contribute to the development and progression of various hematological malignancies. This review will provide an overview of the impact of the immunopathogenic function of IL-15 by studying its role in cell survival, proliferation, inflammation, and treatment resistance. We will also review therapeutic approaches for inhibiting IL-15 in blood cancers.